Assessment of land use land cover change and its impact on variations of land surface temperature in Atlanta, USA - Dipesh Oli; Buddhi Gyawali; Basanta Neupane; Samuel Oshikoya (Environmental and Sustainability Indicators)
Urbanization has significantly altered land use land cover (LULC), changing patterns and contributing to rising land surface temperature (LST), thereby intensifying the urban heat island effect. This study aims to assess spatiotemporal trends of LULC and LST in Atlanta, Georgia, using Landsat imageries during the 2001–2021 period. This study utilized a supervised random forest classifier for mapping LULC. Geographically weighted regression (GWR) and multiscale geographically weighted regression (MGWR) were employed to assess the impact of LULC classes on LST variation. It was found that built-up areas expanded by 8.76 %, and forests, open space, agricultural lands, and open water decreased by 11.5 %, 4.1 %, 23.1 %, and 6.1 %, respectively, over two decades. The mean LST increased by 4.63 °C. Spatial autocorrelation analysis showed consistent high-high clustering of LST in core urban areas, reflecting intensified urban heat island effect. The MGWR model outperformed the GWR model with higher R2 and lower AIC. The MGWR model revealed a spatially varying relationship between LST and LULC classes, highlighting their non-stationary interaction. It demonstrated that built-up areas significantly contributed to increased LST. In contrast, forests and open spaces exhibited substantial cooling effects, underscoring the necessity of preserving green and open spaces to mitigate the adverse impact of increasing LST in urban settings. This study highlighted that the intensification of urban thermal environments is driven by alterations in land use and land cover patterns and the expansion of urban areas.